Utilization of Minimum Quantity Lubrication (MQL) with Water in CBN Grinding of Steel - Belentani, Rafael de Mello [UNESP]; Funes Junior, Hamilton [UNESP]; Canarim, Rubens Chinali [UNESP]; Diniz, Anselmo Eduardo; Hassui, Amauri; Aguiar, Paulo Roberto [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2014)
The use of cutting fluids is fundamental to machining processes, mainly when it comes to high heat generation, which is the case of grinding. Thus, lubrication and cooling provided by cutting fluids improve the final quality of the workpiece. However, cutting fluid usage provide some drawbacks concerning environmental, costs and health issues. Therefore, new methods for application and optimization of cutting fluids are being researched aiming to reduce the amount of fluid used, as well as the minimization of cutting fluid hazards. The present study analyzes the behavior of a recently proposed optimization method, up to now only tested in turning, which consists of adding water to minimum quantity lubrication (MQL). Three different proportions were tested in this study: 1/1, 1/3 and 1/5 parts of oil per parts of water. The following output variables were evaluated: surface roughness, roundness errors, grinding power and diametric wheel wear. Also, optical microscopy and microhardness measurements were conducted, in order to detect burns and surface alterations. The obtained results were also compared to conventional (flood coolant) cooling-lubrication and traditional MQL (without water). MQL with water (1/5) presented better results of surface roughness and roundness errors, when compared to traditional MQL, and the results are very close to when using flood coolant. For grinding power and wheel wear, the results for MQL with water (1/5) were the best among the tested conditions.
Keywords: grinding; minimum quantity lubrication (MQL); cutting fluid optimization; MQL with water